2021
DOI: 10.1002/fsn3.2397
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 alleviates cognitive impairment through regulating inflammatory stress in db/db mice

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Another study revealed age-induced memory deficits could be reversed with cholecalciferol supplementation with corresponding increases in hippocampal BDNF and NGF expression [ 71 ]. In a model of type 2 diabetes in mice, BDNF and phosphorylation of its downstream effector CREB are reduced in the brain, and cholecalciferol restores these and associated behavioural deficits [ 72 ].…”
Section: Vitamin D and Normal Brain Developmentmentioning
confidence: 99%
“…Another study revealed age-induced memory deficits could be reversed with cholecalciferol supplementation with corresponding increases in hippocampal BDNF and NGF expression [ 71 ]. In a model of type 2 diabetes in mice, BDNF and phosphorylation of its downstream effector CREB are reduced in the brain, and cholecalciferol restores these and associated behavioural deficits [ 72 ].…”
Section: Vitamin D and Normal Brain Developmentmentioning
confidence: 99%
“…More and more evidence shows that vitamin D not only participates in calcium and phosphorus metabolism, but also participates in many biological reactions other than bone metabolism, including a series of nervous system regulation processes 30 . Accumulating evidence has shown that vitamin D deficiency is associated with cognitive decline 31 . Mechanistically, vitamin D seems to regulate the brain's oxidative response by modulating cell growth factors 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…30 Accumulating evidence has shown that vitamin D deficiency is associated with cognitive decline. 31 Mechanistically, vitamin D seems to regulate the brain's oxidative response by modulating cell growth factors. 32,33 Durk et al showed that vitamin D treatment significantly reduced plaque density in the cortex and hippocampus, improved cognitive function, and enhanced learning and memory in rodent models of Alzheimer's disease and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective, anti-inflammatory, and antioxidant properties of vitamin D have been widely studied in preclinical studies, which then led to the hypothesis that vitamin D could serve as a potentially modifiable risk factor for cognitive decline and neurodegenerative diseases [19][20][21], including the POCD 5 Mediators of Inflammation [5,8,22]. However, preclinical research on the function of VD3 in the development of POCD is still limited.…”
Section: Discussionmentioning
confidence: 99%